Current insights in molecular characterization of non-alcoholic fatty liver disease and treatment - Che, Wensheng; Zhao, Ming; Li, Xiaoqing; Li, Chunlong; Cho, William C.; Yu, Shan (Frontiers in Endocrinology, 2022)
There is a continuously rising incidence of non-alcoholic fatty liver disease (NAFLD) around the world, which parallels the increasing incidence of metabolic diseases. NAFLD is a range of liver conditions that contains simple non-alcoholic fatty liver and advanced non-alcoholic steatohepatitis. In serious cases, NAFLD may develop into cirrhosis or even liver cancer. NAFLD has an intense relationship with metabolic syndrome, type 2 diabetes mellitus. It is known that gut microbiota, and functional molecules such as adenosine monophosphate-activated protein kinase JNK, and peroxisome proliferator-activated receptors (PPARs) in progressing and treating NAFLD. Traditionally, the conventional and effective therapeutic strategy is lifestyle intervention. Nowadays, new medicines targeting specific molecules, such as farnesoid X receptor, PPARs, and GLP-1 receptor, have been discovered and shown beneficial effects on patients with NAFLD. In this article, we focus on the molecular mechanisms and therapeutic approaches to NAFLD.